2001
DOI: 10.1038/sj.onc.1204749
|View full text |Cite
|
Sign up to set email alerts
|

CRBP suppresses breast cancer cell survival and anchorage-independent growth

Abstract: We showed earlier that cellular retinol-binding protein (CRBP) expression is downregulated in a subset of human breast cancers. We have now investigated the outcome of ectopic CRBP expression in MTSV1-7 cells, a SV40 T antigen-transformed human breast epithelial cell line devoid of endogenous CRBP expression. We found that: (i) CRBP did not inhibit adherent cell growth but suppressed foci formation in post-con¯uent cultures and colony formation in soft agar; (ii) this e ect was due to CRBP inhibition of cell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 28 publications
3
41
1
6
Order By: Relevance
“…Briefly, 10,000 cells were seeded in 0.3% Noble Agar, keratinocyte serum-free medium supplemented with bovine pituitary extract and insulin-like growth factor (Invitrogen) fungizome, penicillin-streptomycin, and L-glutamine. Colony number was determined using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide dye staining as described (26).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 10,000 cells were seeded in 0.3% Noble Agar, keratinocyte serum-free medium supplemented with bovine pituitary extract and insulin-like growth factor (Invitrogen) fungizome, penicillin-streptomycin, and L-glutamine. Colony number was determined using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide dye staining as described (26).…”
Section: Methodsmentioning
confidence: 99%
“…The c-srcspecific kinase inhibitor PP1 [4-amino-5-(4-methylphenyl)-7-(t-butyl)pyrazolo(3,4-D)pyrimidine] was obtained from Biomol and the inactive structural analogue PP3 [4-amino-7-phenylpyrazol(3,4-D)pyrimidine] was purchased from CalBiochem (San Diego, CA). Cell viability was determined using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide dye staining as described (23).…”
Section: Methodsmentioning
confidence: 99%
“…The loss of CRBP1 could diminish RA transport and result in blockage of the transcription of RA-responsive genes that regulate cell proliferation. However, previous studies have supported the hypothesis that CRBP1 could be involved in the promotion of apoptosis through an increase in the RA metabolism in breast cancer cell lines (17,24,25). As the suppression of apoptosis played a key role in BC carcinogenesis (26), the observed low expression of CRBP1 in our study could disrupt the RA-mediated apoptosis pathway in BC.…”
Section: Discussionmentioning
confidence: 31%
“…Many studies have shown that it is down-regulated and functions as a tumor suppressor gene (11)(12)(13)(14)(15)(16)(17)(18), whereas it is up-regulated in cervical cancer (19). In breast cancer, CRBP1 down-regulation promoted the progression of tumors through the inhibition of RA receptor activity (24). In terms of BC, RA treatment effectively reduced the recurrence rate and increased the survival time of superficial BC patients (26,27).…”
Section: Discussionmentioning
confidence: 99%